Foundations of sports coaching - Robinson, Paul E. 4 0 16; 5 (London : Routledge, 2010)
Provides an overview of sports coaching, featuring tips, techniques, tactics, international case studies, and information on planning and management, performance analysis, basic principles in anatomy and physiology, and more.
Includes bibliographical references (p. 217-228) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Training of.;Training. -- Coaching (Athletics).;Coaches (Athletics);Coaching (Athletics);Coaching (Athletics); 20; 2